1994
DOI: 10.1111/j.1476-5381.1994.tb13082.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of human EP3 receptors: evidence of three variants with differing carboxyl termini

Abstract: 1 The polymerase chain reaction (PCR) was used in combination with plaque hybridization analysis to clone four variants of the EP3 prostaglandin receptor from a human small intestine cDNA library. 2 Three of these variants, i.e. the EP3A, EP3E and EP3D, share the same primary amino acid sequence except for their carboxyl termini, which diverge from one another at the same point, approximately 10 amino acids away from the end of the seventh membrane spanning domain of the receptor. The fourth variant (EP3A1) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 23 publications
1
85
0
Order By: Relevance
“…The ATG assigned as the initiation codon matched well to the Kozak consensus sequence for translation initiation [17]. Analysis of the predicted amino acid sequence indicated that it possesses seven hydrophobic segments typical of guanine nucleotide-binding protein-coupled rhodopsin-type receptors, and is 86% identical to that of the human EP2 receptor [11]. Two potential N-glycosylation sites [18] were found in the N-terminal and the first extracellular loop regions.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The ATG assigned as the initiation codon matched well to the Kozak consensus sequence for translation initiation [17]. Analysis of the predicted amino acid sequence indicated that it possesses seven hydrophobic segments typical of guanine nucleotide-binding protein-coupled rhodopsin-type receptors, and is 86% identical to that of the human EP2 receptor [11]. Two potential N-glycosylation sites [18] were found in the N-terminal and the first extracellular loop regions.…”
Section: Resultsmentioning
confidence: 67%
“…Degenerate PCR primers, 5'-CTGGGATCCATGCTCATGCT(CG)TT(CT)GC(ACGT)ATGG-C-3' and 5'-GCAGAATTCAGACGGCGAA(CG)GT(AG)AT(GTF GTCAT-3', corresponding to the putative third and sixth transmembrane domains of the human EP 2 receptor [11] were synthesized. The thermal cycle program was 94°C for 0.8 min, 48°C for 1 min, 72°C for 3 min for the first 2 cycles, 94°C for 0.8 min, 50°C tbr 1 min, 72°C for 0014-5793/95/$9.50 ~ 1995 Federation of European Biochemical Societies.…”
Section: Ampl(hcation Of a Edna Fi'agment O[' The Mouse Ep: Receptor Bymentioning
confidence: 99%
See 1 more Smart Citation
“…receptors A 930 bp RT-PCR fragment of the EP4 receptor [18] (primers EP4-3F and -2R) and a 1149 bp fragment of the EP2 receptor [19] (primers EP2-3F and -2R) were cloned into the Smal restriction site of pBlueScript. From the construct containing the EP4R insert, a 171 bp fragment was removed by restriction enzyme digestion with BssHlI (at positions 1037 and 1208, GenBank accession number L25124), followed by gel electrophoresis, extraction (Genomed, Bad Oeynhausen, Germany) and religation of the new construct.…”
Section: Generation Of Internal Pcr Standards For the Ep2 And Ep4mentioning
confidence: 99%
“…Since the Gs-linked EP2 receptor has a lower affinity for PGE2 than the Gs-linked EP4 receptor, this would implicate a high number of the high affinity EP4 receptor (K,l 1-2 nM [18,23]) and a small number of the low affinity EP2 receptor (Kd 100 nM [19]). This contrasts with findings of a highly abundant low affinity (Kd 137 nM) and a rare high affinity (Kd 3.1 nM) PGEz receptor on U-937 cells [24].…”
Section: Validation Of Quantitative Competitive Rt-pcr and Thementioning
confidence: 99%